ESTUDO DO EFEITO DO ÓXIDO DE ESTRÔNCIO NA BIOATIVIDADE DO SISTEMA VÍTREO CÁLCIO-SÓDIO-BORATO - GUIMARÃES NETO, Floriano (2019)
In this work the replacement of calcium and sodium oxide by strontium oxide in the calcium sodium-borate bioactive glasses was studied to evaluate the bioactivity of the system and the control of the ion release in SBF. Five samples were prepared by the melt quenching technique, varying the concentration of SrO from 0 to 20 % wt, in order to understand how the properties of the matrix would be altered with the strontium insertion and how the ionic leaching process in SBF occurs. The diffractograms carried out for the samples before the immersion in SBF confirmed their amorphous nature. The density data showed an increase as CaO and Na2O were replaced by SrO, while the molar volume decreased in the same proportions. The infrared spectra of the samples, before immersion in SBF, showed three bands characteristic of borate glasses vibrations of BO3 and BO4 group bonds. The specific heat data did not show significant variations. However, the N4 values showed an increase of connectivity in the borate structures indicating an increase of BO4 units due to the influence of Sr, decreasing the chemical reactivity of the glasses. The pH data showed an exponential behavior with lower values for the samples with higher amount of SrO and higher pH for the sample without strontium indicating a control of the ions releasing in SBF. The FTIR and XRD data obtained after of the immersion of samples in SBF confirmed the bioactivity of the materials with formation of hydroxyapatite (HA) on their surfaces. These results indicate that strontium doped calcium-sodium-borate glasses have lower rates of ionic leaching in SBF when compared to the sample without of strontium. Therefore, it is evident that strontium can control the release of ions by inducing changes in connectivity in the vitreous matrix.